Virtual machine scheduling strategy based on dual-speed and work vacation mode and its parameter optimization - Shun-fu JIN; Shan-shan HAO; Bao-shuai WANG (Tongxin xuebao)
Due to the increasingly strict environmental standards,high pollution and high energy consumption have become the significant factors restricting the development of cloud data centers (CDC).Under the premise of guaranteeing the quality of service (QoS) of CDC,dynamic power management (DPM) technology was applied,synchronous multiple working sleep mode was introduced,and a novel virtual machine (VM) scheduling strategy was proposed.By establishing a two-dimensional continuous-time Markov stochastic model with adaptive service rate and synchronous multiple work vacations,and using the method of a matrix geometric solution,the performance of the VM scheduling strategy was evaluated in terms of energy saving level and average delay of requests.Numerical results with analysis and simulation verify the energy saving effectiveness of the VM scheduling strategy.In order to achieve a reasonable balance between the response performance and the energy-saving effect,a system utility function was constructed from the perspective of economics and design a researching algorithm of the sleep parameter based on the firefly algorithm(FA).